Evaluation of Accidents Occurrence and Associated Risk Factors among 11-14-Year-Old Children in Isfahan Province, Iran, in Year 2015 - Narges Motamedi (مجله دانشکده پزشکی اصفهان, 2019)
Background: Increased rate of accidents among students on a hand, and progression of technology on the other hand, demonstrate the necessity of individual health assessment among them. The current study aimed to assess the frequency of accident (traffic and non-traffic) occurrence and its associated risk factors among 11-14-year-old students in Isfahan Province, Iran, in year 2015.